2008
DOI: 10.1094/cchem-85-2-0218
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Lipid Stability in Whole Wheat Flour by Lipase Inactivation and Antioxidant Retention

Abstract: Cereal Chem. 85(2):218-223The purpose of this study was to determine the effectiveness of dry heat, steam, and microwave treatments in decreasing lipase activity, while retaining antioxidant activity, to stabilize whole wheat flour against lipid degradation during storage. Bran was heat-treated in 230-g batches using four levels (exposure times) for each of the three treatment methods. Lipase activity and antioxidant activity were quantified for all treatment combinations. None of the treatments significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 16 publications
7
50
0
1
Order By: Relevance
“…Bookwalter et al [5] reported complete inactivation of lipid enzymes in whole proso millets by heat processing with steam-jacketed paddle conveyor having temperatures up to 110°C. The higher reduction (96 %) of lipase activity in whole wheat flour during steam heating as compared to the microwave heating (93 % reduction) for similar duration (60 s) was also observed by Rose et al [26]. Keying et al [13] also observed lipase inactivation in naked oat kernels during microwave heating and correlated with temperature and exposure time.…”
Section: Pearl Millet Grain Characteristicssupporting
confidence: 73%
“…Bookwalter et al [5] reported complete inactivation of lipid enzymes in whole proso millets by heat processing with steam-jacketed paddle conveyor having temperatures up to 110°C. The higher reduction (96 %) of lipase activity in whole wheat flour during steam heating as compared to the microwave heating (93 % reduction) for similar duration (60 s) was also observed by Rose et al [26]. Keying et al [13] also observed lipase inactivation in naked oat kernels during microwave heating and correlated with temperature and exposure time.…”
Section: Pearl Millet Grain Characteristicssupporting
confidence: 73%
“…A previous study on germ stabilization described the inactivation of wheat germ lipase at 175°C in a forced draft oven (Rose et al 2008). Taking into account this previous study along with the temperature profiles and the features of the IR equipment of the present investigation, the following ranges of independent variables were selected to reach the optimum processing conditions: IRRI from 3000 to 9000 W/m 2, GD from 0.2 to 0.1 m and TT from 1 to 3 min.…”
Section: Resultsmentioning
confidence: 99%
“…Since the lipase activity is concentrated in the bran, this fraction can be heated separately and then added to wheat flour in the proper proportions to make whole wheat flour (Rose et al, 2008). This allows for the inhibition of lipase without risking influencing the flour functional properties.…”
Section: Carbohydrate Degradation During Whole Wheat Flour Storagementioning
confidence: 99%
“…Therefore, if lipase is denatured, lipoxygenase is also denatured. Vetrimani and Haridas Rao (1990) reduced lipase activity in wheat bran by 40% by heating at 175 C for 40 min Rose et al (2008) reported 74, 93 and 96% reduction in lipase activity when wheat bran was dry heated at 175 C for 25 min, 60 s of microwave (1000 W), or 60 s of steam, respectively.…”
Section: Carbohydrate Degradation During Whole Wheat Flour Storagementioning
confidence: 99%